Generalized boundary triples, II. Some applications of generalized boundary triples and form domain invariant Nevanlinna functions - Derkach, Volodymyr; Hassi, Seppo; Malamud, Mark (Wiley, 2022)
The paper is a continuation of Part I and contains several further results on generalized boundary triples, the corresponding Weyl functions, and applications of this technique to ordinary and partial differential operators. We establish a connection between Post's theory of boundary pairs of closed nonnegative forms on the one hand and the theory of generalized boundary triples of nonnegative symmetric operators on the other hand. Applications to the Laplacian operator on bounded domains with smooth, Lipschitz, and even rough boundary, as well as to mixed boundary value problem for the Laplacian are given. Other applications concern with the momentum, Schrödinger, and Dirac operators with local point interactions. These operators demonstrate natural occurrence of -generalized boundary triples with domain invariant Weyl functions and essentially selfadjoint reference operators A0.
Keywords: boundary triple; boundary value problem; Dirichlet-to-Neumann type map; Green's identities; resolvent; selfadjoint extension; symmetric operator; trace operator; Weyl function; fi=Matematiikka|en=Mathematics|